1995
DOI: 10.1042/bj3110119
|View full text |Cite
|
Sign up to set email alerts
|

Expression of stress proteins and mitochondrial chaperonins in chronically stimulated skeletal muscle

Abstract: Molecular chaperones and cytosolic stress proteins are actively involved in the stabilization, import and refolding of precursor proteins into mitochondria. The purpose of the present study was to evaluate the relationship between mitochondrial content under steady-state conditions, and during the induction of organelle biogenesis, with the expression of stress proteins and mitochondrial chaperonins. A comparison of steady-state levels of mitochondrial enzyme activity [cytochrome c oxidase (CYTOX)] with chaper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 37 publications
10
80
0
1
Order By: Relevance
“…Thus, it appears that HSPs may play a role in protection not only in cardiac, but also in skeletal muscle. In mammalian muscle cells, the 60 kDa family of HSPs is increased both after acute exhaustive exercise (Locke et al 1990;Salo et al 1991) and 10 days of chronic contractile activity (Ornatsky et al 1995). Our data indicate that basal HSP 60 levels were 44, 43 and 67% greater in the LV, RV and SOL, respectively, of trained versus untrained rats, but they were not changed in AT or LG.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Thus, it appears that HSPs may play a role in protection not only in cardiac, but also in skeletal muscle. In mammalian muscle cells, the 60 kDa family of HSPs is increased both after acute exhaustive exercise (Locke et al 1990;Salo et al 1991) and 10 days of chronic contractile activity (Ornatsky et al 1995). Our data indicate that basal HSP 60 levels were 44, 43 and 67% greater in the LV, RV and SOL, respectively, of trained versus untrained rats, but they were not changed in AT or LG.…”
Section: Discussionmentioning
confidence: 46%
“…The physiological stress of exercise (Locke et al 1990(Locke et al , 1995Salo et al 1991) and exercise-like activities (Ornatsky et al 1995;Neuffer et al 1996) acutely elevates HSP expression. Locke et al (1990) have demonstrated that rodent skeletal muscle HSPs are increased after one bout of exhaustive exercise.…”
mentioning
confidence: 99%
“…In turn, activity-induced changes have been observed in Tom20, Hsp60 and mtHSP70 protein and cpn10 mRNA levels, as well as cytosolic concentrations of Hsp70 and MSF (13)(14)(15). Coincident with these changes is acceleration in the rate of protein import into the matrix.…”
Section: Exercise Effects On Pimmentioning
confidence: 87%
“…Mortalin is ubiquitously expressed, and so far has been detected in all mammalian cells analysed. This protein has been implicated in stress response (Ornatsky et al, 1995), muscle activity (Ibi et al, 1996), mitochondrial biogenesis (Schneider and Hood, 2000), control of cell proliferation (Kaul et al, 2000b), intracellular trafficking (Mizukoshi et al, 2001), differentiation (Xu et al, 1999) and tumorigenesis (Takahashi et al, 1994;Kaul et al, 1998;Wadhwa et al, 2006). Expression level of mortalin is frequently increased in tumours (Kaul et al, 2002;Dundas et al, 2005), where it is believed to cause inactivation of tumour suppressor protein TP53 .…”
Section: Discussionmentioning
confidence: 99%